(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2008)
In Bangladesh some researchers have done several studies to find the correlation of simple diffuse goiter with arsenic level but no one conducted any study to find the differences of urinary iodine, urinary arsenic, radioiodine uptake, the thyroid stimulating hormone (TSH) and free thyroxin (FT4) levels between goitrous and non goitrous. That is why, in this research an attempt has been made to compare the urinary iodine, urinary arsenic, radioiodine uptake, TSH and FT4 levels between experimental group with simple diffuse goiter and healthy control group. In this study another purpose has also been made to find the associations between different pairs of variables for both experimental and control group. In this study we have tried to find the impacts of arsenic level on simple diffuse goiter. This is a case-control analytical study. The study is carried out in the Institute of Nuclear Medicine and Ultrasound, in collaboration with the thyroid out patient department of Bangabandhu Sheikh Mujib Medical University. A total of eighty five (85) subjects are included in the study. Among the 85 subjects, a sample of forty five is considered for experimental group with simple diffuse goiter and another sample of forty is considered for healthy control group without any thyroid disease. From the experimental results it has been found that, the arsenic levels, FT4 and radioiodine uptake levels at 2 hours between the experimental and control groups are significantly different but the urinary iodine levels, TSH levels and radioiodine uptake levels at 24 hours between the experimental and control groups are not statistically different. From the experimental results it has also been found that there is significant differentiation between experimental and controls groups in respect of association between different pairs of variables. In this study, another significant finding is that iodine deficiency is not only the factor of causing simple diffuse goiter, but arsenic level is also one of the most important factor of causing simple diffuse goiter. Key words: Iodine deficiency, Simple diffuse goiter, Urinary arsenic, Statistical analysis, Association, Experimental and Control groups Â DOI = 10.3329/dujps.v7i1.1224 Dhaka Univ. J. Pharm. Sci. 7(1): 89-98, 2008 (June)